Analisis Modus Persekongkolan Tender dalam Tindak Pidana Korupsi Pengadaan Barang dan Jasa Pemerintah - Santi Pratama Anggraini; Anza Ronaza Bangun (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This study analyzes the practice of tender rigging, which is a dominant form of irregularity in government procurement of goods and services. The study focuses on identifying and analyzing the modus operandi, which includes the use of borrowing flags, document manipulation, leaking of the Self-Estimated Price (HPS), and price agreements between participants (tender arisan). The research findings reveal that the collusion occurs in two patterns: vertical between providers and the committee, and horizontal between providers. Both patterns fulfill the elements of unlawfulness as stipulated in Articles 2 and 3 of the Corruption Eradication Law. This practice of tender rigging causes significant state financial losses and undermines fair business competition. Therefore, the effectiveness of law enforcement depends heavily on accurate proof of state losses and good coordination between law enforcement officials and the Business Competition Supervisory Commission to ensure fair resolution in accordance with applicable legal provisions.